Методи формування правового мислення при вивченні правових дисциплін студентами неюридичних спеціальностей - Нестеренко, Олена Миколаївна; Нестеренко, Елена Николаевна; Nesterenko, Olena; Горбова, Наталя Аркадіївна; Горбова, Наталья Аркадьевна; Horbova, Natalia; Рибальченко, Ніна Павлівна; Рыбальченко, Нина Павловна; Rybalchenko, Nina; Скляров, Роман Васильович; Скляров, Роман Васильевич; Skliarov, Roman; et al. (ТДАТУ, 2021)
UK : У статті розглянуті питання актуальності отримання правових знань студентами неюридичних спеціальностей через підвищення рівня правового мислення, що в майбутньому буде сприяти формуванню правової компетентності майбутніх спеціалістів. EN : The article considers the relevance of obtaining legal knowledge by students of non-legal specialties by increasing the level of legal thinking, which in the future will contribute to the formation of legal competence of future professionals. Given this, it is proposed to apply new methods of mastering the material of legal disciplines, which will significantly help to use the acquired legal knowledge in professional activities.
Methods of formation of legal thinking in the study of legal disciplines by students of non-legal specialties
Keywords: правове мислення; правове виховання; правова свідомість; правова освіта; методи навчання; методи правового навчання; legal thinking; legal education; legal consciousness; legal education; teaching methods; legal training methods